Patients’ and providers’ perspectives on medication relatedness and potential preventability of hospital readmissions within 30 days of discharge - Uitvlugt, Elien B. (Health Expect, 2019)
BACKGROUND: Hospital readmissions are increasingly used as an indicator of quality in health care. One potential risk factor of readmissions is polypharmacy. No studies have explored the patients’ perspectives on the medication relatedness and potential preventability of their readmissions. OBJECTIVE: To compare the patients’ perspectives on the medication relatedness and potential preventability of their readmissions with the providers’ perspectives. METHODS: Patients unplanned readmitted within 30 days after discharge at one of the participating departments of OLVG Hospital in Amsterdam were interviewed during their readmission. Patients’ perspectives regarding medication relatedness of their readmissions, the potential preventability, possible preventable interventions, and satisfaction with medication information were examined. Health‐care providers also reviewed files of these readmitted patients. Primary outcome was the percentage of medication‐related and potentially preventable readmissions according to the patient vs the provider. Descriptive data analysis was used. RESULTS: According to patients, 36 of 172 (21%) readmissions were medication‐related, and of these, 21 (58%) were potentially preventable. According to providers, 26 (15%) readmissions were medication‐related and 6 (23%) of these were potentially preventable. Patients and providers agreed on the medication relatedness in 11 of the 172 readmissions, and in two of these, agreement on the potential preventability existed. According to patients, preventive interventions belonged mostly to the hospital level, followed by the primary care level and patient level. CONCLUSION: Patients and providers differ substantially on their perspectives regarding the medication relatedness and preventability of readmissions. Patients were more likely to view medication‐related readmissions as preventable.